The acquisition of direct object scrambling and clitic placement : syntax and pragmatics - Schaeffer, Jeannette C. (Language acquisition & language disorders, 2000)
This book offers a new contribution to the debate concerning the "real time acquisition" of grammar in First Language Acquisition Theory. It combines detailed and quantitative observations of object placement in Dutch and Italian child language with an analysis that makes use of the Modularity Hypothesis. Real time development is explained by the interaction between two different modules of language, namely syntax and pragmatics. Children need to build up knowledge of how the world works, which includes learning that in communicating with someone else, one must realize that speaker and hearer.